2014
DOI: 10.2355/isijinternational.54.2394
|View full text |Cite
|
Sign up to set email alerts
|

Martensite Nucleation at Grain Boundaries Containing Intrinsic Grain Boundary Dislocations

Abstract: It is shown that grain boundaries containing intrinsic grain boundary dislocations act as preferential nucleation site for the martensitic transformation. The microstructure and crystallography of BCC α'-martensite formed in a sensitized AISI 304 stainless steel was studied in detail by means of convergent beam Kikuchi pattern analysis. The orientation relationship between martensite and austenite was determined to be Kurdjumov-Sachs type. The presence of intrinsic grain boundary dislocations was observed at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
0
9
1
4
Order By: Relevance
“…The experimental studies have shown that the grain boundaries (GBs) and triple junctions (TJs) are additional heterogeneities favourable for the M nucleation in the polycrystalline samples of such phase-changing materials [27][28][29][30][31][32][33][34][35][36][37], which was also confirmed through atomistic simulations [38][39][40][41][42]. In particular, the parameters such as the grain orientation distribution (see, e.g.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…The experimental studies have shown that the grain boundaries (GBs) and triple junctions (TJs) are additional heterogeneities favourable for the M nucleation in the polycrystalline samples of such phase-changing materials [27][28][29][30][31][32][33][34][35][36][37], which was also confirmed through atomistic simulations [38][39][40][41][42]. In particular, the parameters such as the grain orientation distribution (see, e.g.…”
Section: Introductionmentioning
confidence: 78%
“…The temperatures of M nucleation from the GBs are usually significantly higher than the homogeneous transformation temperature of M [28,29]. The start and finish temperatures for both the forward (A → M) and the reverse (M → A) transformations from the tilt GBs are much higher than that for the twist GBs [28,32,38,39]. The reason for this was attributed to the local stress fields associated with the intrinsic dislocations in the low angle tilt GBs [28,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26) This change of the microstructures in steel from austenite to martensite is called martensitic transformation. [29][30][31] The hardening phenomenon of steel through this martensitic transformation is called martensite hardening in this study.…”
Section: Influence Of Natural Scientific Understanding Level About Physical Phenomena In Steelmentioning
confidence: 99%
“…A preference for heterogeneous nucleation in Martensitic Transformations (MT) has been evidenced by a wide body of experimental explorations on steels [1][2][3], shape-memory alloys [4][5][6], ceramics [7][8], etc. The heterogeneous processes of nucleation and subsequent growth at various defects present distinct microstructure [9][10], diverse transformation pathways [11][12], and hence give rise to different properties of materials [13][14].…”
Section: Introductionmentioning
confidence: 99%